SISTEM INFORMASI REKAPITULASI DATA REALISASI INVESTASI DI DINAS PENANAMAN MODAL, ESDM DAN TRANSMIGRASI PROVINSI GORONTALO - Abrianto Nusi; Moh Hidayat Koniyo; Manda Rohandi (Diffusion: Journal of Systems and Information Technology, 2021)
Abstract The recruitment system is essential to improve service to a job or activity. The activity of collecting data on the realization of investment at the Gorontalo Province Investment, ESDM, and Transmigration Office uses Microsoft Excel. This recapitulation activity has several obstacles that are the background of this research. The constraints experienced are the slow process of recapping, piling up of files so that there is a risk of damage or loss of data, and unable to display investment charts every quarter. The method used in this research is the prototype method. The final results obtained in this study are in the form of an information system for recapitulation of investment realization data to make it easier for the government to manage recapitulation activities, monitor the progress of investment every quarter, and be able to determine the budget plan to be set for the following year and data storage to be more effective and safer. Keywords: Recapitulation, Recapitulation Information System, Realization of Investment, Investment, Prototype.